User Acceptance of Automatic Speech Recognition in University Oral English Instruction: An Analysis from the Perspective of Learners’ Learning Styles - Fan, Yuan (Journal of Social Science and Humanities, 2025)
Situated in an era when artificial intelligence has been applied across a wide range of fields, the domain of foreign language education has also gradually integrated new technologies. One representative technology applied in this field is Automatic Speech Recognition (ASR). The present study, based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model, designs a user acceptance questionnaire for ASR and aims to explore the impact of learning styles on students’ acceptance levels. The results demonstrate that visual, introverted, leveler and deductive learning styles are positively correlated with user acceptance of ASR; kinesthetic and sharpener learning styles are negatively linked to the user acceptance; while auditory and extraverted learning styles do not have significant impact on user acceptance of ASR. The results of this study provide important theoretical foundations and practical guidance for the application of ASR in foreign language education, particularly oral English instruction.